2022
DOI: 10.3390/ijms23031796
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis Uncovers Osteoblast Factor Growth Differentiation Factor 10 as Mediator of Vascular Smooth Muscle Cell Phenotypic Modulation Associated with Plaque Rupture in Human Carotid Artery Disease

Abstract: (1) Background: Vascular smooth muscle cells (VSMCs) undergo a complex phenotypic switch in response to atherosclerosis environmental triggers, contributing to atherosclerosis disease progression. However, the complex heterogeneity of VSMCs and how VSMC dedifferentiation affects human carotid artery disease (CAD) risk has not been clearly established. (2) Method: A single-cell RNA sequencing analysis of CD45− cells derived from the atherosclerotic aorta of Apolipoprotein E-deficient (Apoe−/−) mice on a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 129 publications
0
19
0
Order By: Relevance
“…Ten articles ( 20 , 27 , 28 , 31 , 37 , 41 , 45 47 , 50 ) addressed the role of SMCs in atherosclerosis and vascular inflammation. Four of these articles ( 20 , 45 , 46 , 50 ) utilized single-cell sequencing exclusively, one ( 31 ) utilized next-generation RNA sequencing exclusively, one ( 47 ) utilized next-generation micro-RNA sequencing, and the remaining four ( 27 , 28 , 37 , 41 ) utilized a combination of these methodologies, including the use of ChIP-Seq ( 27 , 28 , 37 ), ATAC-Seq ( 28 ) and CITE-Seq ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten articles ( 20 , 27 , 28 , 31 , 37 , 41 , 45 47 , 50 ) addressed the role of SMCs in atherosclerosis and vascular inflammation. Four of these articles ( 20 , 45 , 46 , 50 ) utilized single-cell sequencing exclusively, one ( 31 ) utilized next-generation RNA sequencing exclusively, one ( 47 ) utilized next-generation micro-RNA sequencing, and the remaining four ( 27 , 28 , 37 , 41 ) utilized a combination of these methodologies, including the use of ChIP-Seq ( 27 , 28 , 37 ), ATAC-Seq ( 28 ) and CITE-Seq ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Brandt et al ( 50 ) undertook single-cell sequencing of CD45 − cells isolated from atherosclerotic aortas of ApoE −/− mice on a normal and high cholesterol diet, with cells categorized based localization to atheroprone and atheroresistant regions (aortic arch and descending thoracic aorta, respectively). Differential regulation of genes was identified in the atheroprone cell cluster based on diet associated with apoptosis, inflammation, atherogenesis among others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of atherosclerosis is complex and involves various cells. With the development of technology in recent years, scRNA-seq has been used to construct an atherosclerosis cell atlas of mice and humans, including immune cells, such as monocytes/macrophages, dendritic cells, T cells, B cells, natural killer (NK) cells, and nonimmune cells, such as VSMCs, ECs, pericytes, and fibroblasts (Cochain et al, 2018;Kim et al, 2018;Winkels et al, 2018;Gu et al, 2019;Depuydt et al, 2020;Burger et al, 2022). Research has revealed cellular heterogeneity and provided new insights into the pathogenesis of atherosclerosis.…”
Section: Scrna-seq Applications In Atherosclerosis Researchmentioning
confidence: 99%
“…Li F. et al (2021) discovered a d-flow-dependent osteogenic phenotype, Spp1 hi SMC, with functions, such as osteoblast differentiation, collagen biosynthesis, and vascular remodeling, which may play a role in d-flow-induced arterial stiffness. A study by (Burger et al, 2022) showed that Lyve-1 resident-like macrophages promoted VSMC transition into osteogenic-like cells by secreting CCL24. In addition, (Kim et al, 2020) performed scRNA-seq on mouse aortic roots and showed that SMC-specific deletion of the aryl hydrocarbon receptor (AHR) resulted in increased expression of Frontiers in Pharmacology frontiersin.org chondrocyte markers (Col2a1 and Alpl) in regulated SMC chondrocytes.…”
Section: Smooth Muscle Cellsmentioning
confidence: 99%